Developed and undeveloped submandibular salivary glands of EBN swiftlet (Aerodramus fuciphagus) - Ibrahim, Muhammad Marwan; Abu Bakar @ Zakaria, Md Zuki; Omar, Abdul Rahman (Faculty of Veterinary Medicine, Universiti Putra Malaysia, 2013)
One of the major salivary gland producing saliva in swiftlet species is the submandibular gland. The developed glands are clearly seen under the lower mandible of the swiftlet. Since it is the largest visible salivary gland, it is considered as the major source of saliva production towards the building of the nest. This study was conducted to find out whether all flying swiftlets are making nest for their offspring. The findings revealed that based on the development of the swiftlets salivary glands, not all the flying swiftlets are able to build nest. Some of them were still juvenile where the glands were undeveloped and some were mature and active birds where the glands were well developed.